Spinal myelopathies and their contribution to enteric dysfunction - Momin Ahmed; Diana Feier; Luca Bertola; Brian Kent; Chase Comprosky; Connor Rupp; Brandon Lucke-Wold (Exploration of Neuroscience)
Spinal myelopathies, characterized by neurological deficits due to spinal compression in the spinal column, are increasingly common in the aging population. Although spinal myelopathies commonly present with sensory and motor deficits, they also manifest with life-debilitating enteric dysfunction associated with increased gastroparesis, constipation, bloating, abdominal pain, neurogenic bowel disease, and bladder and bowel incontinence. That said, the effects of spinal myelopathies on enteric gastrointestinal (GI) function are still poorly understood. This review aims to summarize existing literature concerning spinal myelopathies and their effect on the GI system, including the relevant anatomy and physiology of the nervous systems, etiology of various spinal cord injuries, clinical manifestations, current diagnosis and treatment strategies, and ongoing research concerning the gut-brain-spinal axis. The autonomic nervous system contributes to GI innervation through enteric reflex arcs and communication with the central nervous system (CNS) via spinal nerves. When spinal cord damage occurs, enteric reflex arcs, autonomic regulation, and gut-brain-spinal axis can become impaired, leading to GI symptoms. Etiologies of spinal myelopathies occur at all spinal levels. Spinal myelopathy includes inflammatory processes, such as multiple sclerosis and infection, and non-inflammatory processes, such as spondylosis, degenerative disc disease, tumors, and traumatic spinal cord injuries. Diagnosis modalities include imaging, particularly MRI, and functional assessments, such as high-resolution anorectal manometry and colonic transit studies. Enteric dysfunction treatment includes non-pharmacological, pharmacological, neuromodulatory interventions, and surgery. These strategies encompass lifestyle modifications, laxatives, prosecretory agents, 5HT4 agonists, vagus nerve stimulation, sympathetic nerve stimulation, colostomy, and ileostomy. Despite these treatment options, ongoing research with pudendal nerve stimulation, transanal irrigation, mesenchymal stem cells, and the relationship between the gut microbiome and gut-brain-spinal nerve axis may be beneficial in understanding spinal cord myelopathy-related enteric dysfunction, diagnosis, and treatment, ultimately improving clinical outcomes and quality of life for those who are affected.